Upscaling: efficient generation of human lung organoids from induced pluripotent stem cells using a stirring bioreactor - Budeus, Bettina; Kroepel, Chiara; Sevindik, Zehra Fatma; Buttler, Luca Fabian; Klein, Diana (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionHuman induced pluripotent stem cells (iPSCs) can be successfully differentiated into complex (three-dimensional) lung spheroids or organoids and have thus proven to be promising in vitro tools that provide a robust system for simulating lung disease and modeling drug response. We previously described a very simple and practical protocol for producing iPSC-derived lung organoids (iPSC-LuOrgs) in ultra-low attachment plates without relying on a gel-like extracellular matrix.MethodsHere, we produced these organoids in a stirred-tank bioreactor equipped with a unique membrane stirrer and compared this type of up-scaled and more automated cultivation with the manual variant. Detailed morphological and molecular analyses, including single-cell RNA sequencing, of the differently generated LuOrgs were performed.ResultsJust like in the manual variant, using the bioreactor morphologically comparable lung organoids could be obtained that showed a very similar cellular composition. This type of generation can also be considered as animal-component-free production.DiscussionThese freely floating LuOrgs are now available in large numbers for the investigation of, for example, cancer therapy approaches as a new and patient-oriented in vitro platform.